AKSEBILITAS PEMANFAATAN PELAYANAN KESEHATAN OLEH PENGGUNA JAMINAN KESEHATAN NASIONAL (JKN) DI PUSKESMAS - Melisa Melisa; Kina Sari, Sofyan Alri Ansyah Tanjung, Fitriani Pramita Gurning (Jurnal Kesehatan, 2024)
One of the main needs of society that is considered important is health. The aim of this research is to find out whether the health services provided by community health centers are adequate and how easy it is for National Health Insurance (JKN) consumers to get health services. This article was prepared using the literature review method, namely summarizing and explaining the contents of previously published sources of findings in accordance with the topic of the author's analysis regarding the implementation of the JKN program and health services at regional health centers. Articles from 2019 to 2023 are used as references, using Google Scholar, Garuda Journal, and Springer Link. The results of this research are that the quality of health services received at the Community Health Center is in accordance with the national health insurance provided by the government. With the existence of the National Health Insurance (JKN) program, it is very useful in health services, patients are seen as the parties who utilize and benefit from these services, and they are also the parties who have the greatest influence on the quality of services provided. The facilities and infrastructure provided by the government are also complete and adequate for use when seeking treatment at the Community Health Center.